Europe at their feet? Free circulation, economic crisis and exit strategies of recent Portuguese emigrants to the European Union - Candeias, Pedro (2017)
One of the rationales of the free circulation of people within the European Union (EU) is the enabling of a larger and more efficient labour market, where workers can move according to economic reasons, regardless of political barriers. The recent economic crisis overcoming the EU that started in 2008 and was aggravated by the financial woes of the Southern countries has been a favourable context to migration changes. The main objective of this paper is to discuss how Portuguese emigrants have behaved during the crisis, revealing their main reasons for leaving, migration strategies, labour insertion, transnational links and future plans